2014
DOI: 10.1142/s0218348x1450008x
|View full text |Cite
|
Sign up to set email alerts
|

On the Visual Complexity of Built and Natural Landscapes

Abstract: In this study, we analyze some critical points of the application of the box-counting method to the evaluation of the fractal dimensions of the natural and built landscapes. A brief theoretical discussion of the eventual drawbacks of the method is supported by experimental results of two box-counting programs applied to classical fractals. The optimized version of the algorithm, based on the results of computations for the classical fractal images, is proposed and employed for the evaluation of the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Fractals are self-repetitive patterns across different spatial scales [38], and they are used as a quantitative measure of visual complexity (e.g. [39]). Nature images have greater amounts of fractals than urban images [40], and fractal properties have been found to be crucial visual drivers of positive response to nature [41], giving rise to the hypothesis that this particular image characteristic may be part of the basis for preference.…”
Section: Introductionmentioning
confidence: 99%
“…Fractals are self-repetitive patterns across different spatial scales [38], and they are used as a quantitative measure of visual complexity (e.g. [39]). Nature images have greater amounts of fractals than urban images [40], and fractal properties have been found to be crucial visual drivers of positive response to nature [41], giving rise to the hypothesis that this particular image characteristic may be part of the basis for preference.…”
Section: Introductionmentioning
confidence: 99%
“…These new results did not convincingly support Bovill's concept of a local ecology being reflected in the surrounding architecture, as the gap in the fractal dimensions of the images analysed was too large to provide compelling evidence. The Amasya data were further tested by others in 2014 [33] and both studies concluded that Bovill's results were limited by the images chosen for analysis. In particular, the selection of images from the original work lacked a clear rationale and the type of logical guidelines for the selection of data required to make such a disparate comparison.…”
Section: Image Requirements For Compared Fractal Dimensionsmentioning
confidence: 99%